Biology of Phlebotomus papatasi (Diptera: Psychodidae) in the Laboratory. Issue 4 (28th October 2014) - Chelbi, I.; Zhioua, E.
Abstract : Details on the productivity and developmental times of a colony of Phlebotomus papatasi Scopoli (Diptera: Psychodidae) over 14 generations are reported and compared with findings of previous studies. The average productivity (percentage of eggs laid that were reared to adults) over six generations at 26–27 and at 29–30°C was 44.08 and 59.53%, respectively. The maximum productivity was 69.5%. The average developmental time over six generations at 26–27 and at 29–30°C was 35 and 26 d, respectively. The minimum developmental time from egg to adults was 25 d. The Tunisian strain of P. papatasi can reproduce autogenously or anautogenously, depending on the availability of a suitable bloodmeal source.